COMPETENCE APPROACH IN THE FORMATION OF EDUCATIONAL PROGRAMS (IN THE EXAMPLE OF THE PHD PROGRAM IN PHILOSOPHY) - Sobol, T. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
This article discusses the main positions and orientations of the European approach to education and the Ukrainian realities of their implementation. The PhD program in philosophy and the main "competence" requirements of the Decree of the Cabinet of Ministers of Ukraine on the procedure for the preparation of applicants for higher education, Ph.D. and Doctor of Science degrees in higher education institutions are analyzed. The importance of forming general and professional competences in philosophy is emphasized not only for the formation of a professional scientist, but also for a highly developed person who is able to study during whole his or her life and easily overcome the social challenges of our time.